FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK SEPEDA POLYGON DI MASA PANDEMI COVID 19 PADA CIVITAS AKADEMIKA UNIVERSITAS MUHAMMADIYAH PONOROGO - Andhi Anarta; Edi Santoso (PROCEEDING UMSURABAYA, 2022)
ABSTRACTThis study aims to determine the effect of brand image, product quality, lifestyle onpurchasing decisions for polygon bicycle products in the academic community of Muhammadiyah University of Ponorogo. The sample in this research is 100 respondents. The testing stages used include instrument testing, coefficient of determination test and hypothesis testing. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that: (1) Brand image has a positive and significant effect on purchasing decisions. (2) Product quality has a positive and significant effect on purchasing decisions. (3) Lifestyle has a positive and significant effect on purchasing decisions. (4) Brand image, product quality, and lifestyle simultaneously have a positiveand significant effect on purchasing decisions.